THE NEED FOR A MORE EFFICIENT USER NOTIFICATION SYSTEM IN USING SOCIAL NETWORKS AS UBIQUITOUS LEARNING PLATFORMS - (:unkn) unknown (ANADOLU UNIV, 2017)
While carrying out formative assessment activities over social network services (SNS), it has been noted that personalized notifications have a high chance of the important post getting lost in the notification feed. In order to highlight this problem, this paper compares within a posttest only quasi-experiment, a total of 104 first year undergraduate students, all of which are prospective ICT teachers, in two groups. A formative assessment system in the ubiquitous learning context is delivered over an SNS in both groups. In the first group, the SNS has been used for the entire assessment task. In the second group, the questions have been delivered and responses were received over mobile phone SMS messages, while the SNS was used solely for providing feedback. The cases were compared in terms of voluntary participation rates and academic success. Both response rates and academic success have been significantly higher in the SMS group. When asked their reasons for not responding to questions; the SNS-only group frequently reported not noticing the questions being sent. This may indicate a flaw in message design for using social networks as LMS's. Sensible use of push-messages is advised.
Keywords: Ubiquitous learning; formative assessment; LMS design; social networking